Economic Accounting of Ethiopian Forests: A Natural Capital Approach - Daiju Narita; Mulugeta Lemenih; Yukimi Shimoda; Alemayehu N. Ayana (Forest Policy and Economics, 2018)
Ethiopia has experienced a long-term deforestation with broad implications for human life and economic activities, but conventional frameworks of economic accounting are not able to assess the country's economic and environmental sustainability in the faceof such deforestation problem. In this study, we attempt an economic accounting of Ethiopian forests based on a welfare-economic framework, which assesseschanges in the value of forests as natural capital. Our estimates suggest that the recent governmentre-greening efforts areyet to increaseforest assets in the value term, although they have expanded the land areas covered by trees in the country.
Keywords: 330; forest; natural capital; environmental accounting; ecosystem services; sustainability